PfFBXO1 is essential for inner membrane complex formation in Plasmodium falciparum during both asexual and transmission stages - Sreelakshmi K. Sreenivasamurthy; Carlos Gustavo Baptista; Christopher M. West; Ira J. Blader; Jeffrey D. Dvorin (Communications Biology)
Abstract Plasmodium species replicate via schizogony, which involves asynchronous nuclear divisions followed by semi-synchronous segmentation and cytokinesis. Successful segmentation requires a double-membranous structure known as the inner membrane complex (IMC). Here we demonstrate that PfFBXO1 (PF3D7_0619700) is critical for both asexual segmentation and gametocyte maturation. In Toxoplasma gondii, the FBXO1 homolog, TgFBXO1, is essential for the development of the daughter cell scaffold and a component of the daughter cell IMC. We demonstrate PfFBXO1 forming a similar IMC initiation scaffold near the apical region of developing merozoites and unilaterally positioned in gametocytes of P. falciparum. While PfFBXO1 initially localizes to the apical region of dividing parasites, it displays an IMC-like localization as segmentation progresses. Similarly, PfFBXO1 localizes to the IMC region in gametocytes. Following inducible knockout of PfFBXO1, parasites undergo abnormal segmentation and karyokinesis, generating inviable daughters. PfFBXO1-deficient gametocytes are abnormally shaped and fail to fully mature. Proteomic analysis identified PfSKP1 as one of PfBXO1’s stable interacting partners, while other major proteins included multiple IMC pellicle and membrane proteins. We hypothesize that PfFBXO1 is necessary for IMC biogenesis, chromosomal maintenance, vesicular transport, and ubiquitin-mediated translational regulation of proteins in both sexual and asexual stages of P. falciparum.